Penggunaan konjungsi pada rubrik opini surat kabar digital Kompas.com edisi Mei 2023 sebagai bahan ajar teks editorial di kelas XII: Studi analisis - I Made Alvin Fadliansyah; Slamet Triyadi; Wienike Dinar Pratiwi (Aksara: Jurnal Bahasa dan Sastra, 2023)
The purpose of this study is to find out the use of conjunctions in the opinion rubric in the May 2023 edition of the Kompas.com digital newspaper and to describe the use of conjunctions in the opinion rubric in the May 2023 edition of the Kompas.com digital newspaper which can be recommended as teaching material for editorial texts in class. XII SMA for the 2023/2024 academic year. This study uses a qualitative approach and descriptive method. The subject of this study was the opinion rubric of the May 2023 edition of the digital newspaper Kompas.com and the object of this study was the use of conjunctions in the opinion rubric of the May 2023 edition of the digital newspaper Kompas.com. Data collection techniques in this study were observation, documentation, and observation. note. Data analysis techniques in this study used three stages, namely data reduction, data presentation, and drawing conclusions. Based on the results of research on the use of conjunctions in the opinion column of the May 2023 edition of the digital newspaper Kompas.com, 239 sentences used 412 types of conjunctions, consisting of 244 data on the use of coordinating conjunctions and 168 data on the use of subordinating conjunctions. The results of research on using conjunctions in the opinion rubric in the May 2023 edition of the digital newspaper Kompas.com can be recommended as teaching material for editorial texts in class XII high school in the 2023/2024 academic year.Â Keywords: conjunctions, rubrics, opinions, digital newspapers, editorial text teaching materials